Perspectives of pregnant women on maternal health information handouts at KwaZulu-Natal sub-district - Thandi M. Dlamini; Siyabonga Dlamini (AOSIS, 2024)
Background: Maternal health information handouts are used by midwives to facilitate health education of pregnant women during their antenatal care (ANC) period. South Africa's Saving Mothers Report 2014 showed that delay in accessing medical help, as a patient-related avoidable factor, accounted for 27% of maternal and neonatal mortality. Aim: To ascertain the perceptions of pregnant women attending ANC in the Msunduzi sub-district in uMgungundlovu District, towards the maternal health information handouts. Setting: The study was conducted at three primary health care (PHC) clinics (two PHC and one CHC [Community Health Care]) that provided ANC in the Msunduzi sub-district KwaZulu-Natal, in 2019. Methods: Using a qualitative approach, focus group discussions (FGDs) were conducted with 10 participants from each clinic. Data were transcribed and analysed using thematic analysis. Results: The themes explored included: availability and access of handouts, usefulness, review of handouts, alternative methods available, and family involvement. Conclusion: The authors concluded that although the maternal information handouts were given to the mothers during their maternal health visits, few of them were aware of these handouts. New strategies should be employed to deliver this vital information, as suggested by mothers. Contribution: The awareness of pregnant mothers about the information handouts contributes to the positive perinatal outcomes at clinic levels.